การพัฒนาโปรแกรมแนะแนวแบบมีส่วนร่วมเพื่อเสริมสร้างความฉลาดทางดิจิทัล สำหรับนักเรียนชั้นมัธยมศึกษาตอนต้น: Development of Participatory Guidance Programs for Enhancing Digital Intelligence for Lower Secondary School Students - Nongluck Kienngam, นงลักษณ์ เขียนงาม (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2021)
งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาสภาพและความต้องการจำเป็นสำหรับการพัฒนาโปรแกรมแนะแนวแบบมีส่วนร่วมเพื่อเสริมสร้างความฉลาดทางดิจิทัลสำหรับนักเรียนชั้นมัธยมศึกษาตอนต้น และพัฒนาโปรแกรมแนะแนวแบบมีส่วนร่วมเพื่อเสริมสร้างความฉลาดทางดิจิทัล กลุ่มตัวอย่างคือผู้บริหาร ครูแนะแนว ผู้ปกครองนักเรียนชั้นมัธยมศึกษาตอนต้น อำเภอเมือง จังหวัดเชียงใหม่ สุ่มตัวอย่างอย่างง่ายจำนวน 23 โรงเรียน เครื่องมือวิจัย คือ แบบสอบถามสภาพและความต้องการจำเป็นสำหรับการพัฒนาโปรแกรมแนะแนว การวิเคราะห์ข้อมูลเพื่อจัดลำดับด้วยวิธี Priority Needs Index นำผลการศึกษามาสร้างโปรแกรมแนะแนวแบบมีส่วนร่วมด้วยการสนทนากลุ่มกับครูแนะแนวได้แผนการจัดกิจกรรมการเรียนรู้จำนวน 10 กิจกรรม จากนั้นได้ให้นักเรียนเข้าร่วมกิจกรรมด้วยวิธีการคัดเลือกตามความสมัครใจจำนวน 3 โรงเรียน โรงเรียนละ 30 คน รวม 90 คน เครื่องมือที่ใช้ได้แก่ โปรแกรมแนะแนวเพื่อเสริมสร้างความฉลาดทางดิจิทัล แบบวัดความฉลาดทางดิจิทัล แบบวัดพฤติกรรมการใช้สื่อสังคมออนไลน์ และแบบสอบถามความพึงพอใจ สถิติที่ใช้ได้แก่ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน การทดสอบไคกำลังสอง (Chi-square) และการทดสอบความแปรปรวนทางเดียวแบบวัดซ้ำ (One-way Repeated Measure MANOVA) ผลการวิจัยพบว่า 1) ความต้องการจำเป็นสำหรับการพัฒนาโปรแกรมแนะแนวเพื่อเสริมสร้างความฉลาดทางดิจิทัล ด้านความมั่นคงทางดิจิทัล มีความต้องการจำเป็นในการพัฒนาสูงที่สุด รองลงมา คือ ด้านการใช้เครื่องมือและสื่อดิจิทัล ด้านความฉลาดทางอารมณ์บนโลกดิจิทัล และด้านสิทธิทางดิจิทัล 2) โปรแกรมแนะแนวเพื่อเสริมสร้างความฉลาดทางดิจิทัลที่ได้สร้างและพัฒนามีความเที่ยงตรงเชิงเนื้อหาจากการประเมินโปรแกรมแนะแนวโดยผู้เชี่ยวชาญจำนวน 5 ท่าน ผลการประเมินโดยรวมอยู่ในระดับเหมาะสมมาก 3) นักเรียนที่เข้าร่วมโปรแกรมแนะแนวมีคะแนนเฉลี่ยความฉลาดทางดิจิทัล ก่อนการเข้าร่วมโปรแกรมแนะแนว (Pretest) และคะแนนหลังการเข้าร่วมโปรแกรมแนะแนว (Posttest) มีความแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.01 และระดับการติดสื่อสังคมออนไลน์มีความแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 และ 4) นักเรียนมีความพึงพอใจที่มีต่อการจัดโปรแกรมแนะแนวทุกด้านอยู่ในระดับมาก The purposes of this research were to investigate needs assessment for the development of participatory guidance programs for enhancing digital intelligence for lower secondary school students, and to develop guidance programs for enhancing digital intelligence of the students. The samples used in this research were administrators, guidance teachers and parents of the students. The research instrument used in this study was the need assessment questionnaire. The Priority Needs Index method was used for analysing of data. The results of this study were used for the development of the effectiveness of the guidance program. The sample used were 90 students from 3 lower secondary schools in Mueang District, Chiang Mai Province, i.e. 30 students from each school. The participated students were voluntarily participation in the activity. The research instrument used in the study were Guidance Programs for Enhancing Digital Intelligence, Digital Intelligence Quotient Measure, Social Media Behavior Measure and Satisfaction Questionnaire. The statistical parameters and methods used for analyzing the collected data were mean, standard deviation, Chi-square test and One-way Repeated Measure MANOVA. The results showed that 1) there was the need for students to develop digital intelligence. The digital security has the highest demand for development, following by digital use and digital emotional intelligence and digital rights. 2) A digital intelligence-enhancing guidance program created and developed with content-accuracy and assessment of the guidance program was evaluated by 5 experts. The evaluated results showed that it was at a very suitable level. 3) The students who participated in the guidance program had average digital intelligence scores; the pre-test scores and the post-test scores were significantly different at the 0.01 confidence level. For the social media addiction levels, the pre-test and post-test were different at the 0.05 confidence level. 4) Students were highly satisfied with their participation in the guidance program.